A safe-at-home benzoin condensation from imitation almond extract - Bishop Michael J.; Vander Woude Jon; Bosscher Mike A. (Chemistry Teacher International, 2023)
COVID-19 remote learning forced instructors to scramble for meaningful organic laboratory experiences safe enough to perform at home. While resources are available for laboratory experiments at home, organic synthesis suffers from issues involving safety, availabilities of reagents, difficulties measuring reagents, and difficulties analyzing products. We report a new take on the classic benzoin condensation using safe and commonly available reagents, capable of being setup with commonly available kitchen materials, and displaying visible and distinctive product. This experiment is aimed at reinforcing concepts of carbonyl chemistry in the undergraduate organic chemistry laboratory.